Molecular detection of cattle and buffalo species meat origin using mitochondrial cytochrome b (Cyt b) gene (Asian Journal of Medical and Biological Research, 2016)
The study was conducted to adopt PCR based technique for identification of species origin from meat samples of cattle and buffalo using mitochondrial cytochrome b (Cyt b) gene fragment. A total of 42 ear tissue and meat samples were collected from different slaughterhouses and farms of Mymensingh, Bogra and Rangpur districts and stored in 96% ethanol at room temperature. Genomic DNA was extracted from all samples using GeNet Bio genomic DNA isolation kit. The average DNA yield of considered samples was found 204.57 ng/?l where the purity ranged from 1.821.99. Two (2) pair species-specific primers were used to amplify Cyt b gene fragments of 472 bp and 124 bp for cattle and buffalo, respectively. The PCR results revealed different species specific amplified fragments which could discriminate between cattle (472 bp) and buffalo (124 bp) species precisely from pure and mixed samples of those species. This study suggests an accurate molecular technique for identification of cattle and buffalo species meat origin and differentiates species present in adulterated meat samples. In conclusion, this DNA based technique could be utilized for prevention of malpractice in slaughterhouse and chain shops and thereby to protect consumers right.Asian J. Med. Biol. Res. June 2016, 2(2): 177-182